Chatbot vs Medical Student Performance on Free-Response Clinical Reasoning Examinations - Strong, Eric; DiGiammarino, Alicia; Weng, Yingjie; Kumar, Andre; Hosamani, Poonam; Hom, Jason; Chen, Jonathan H (JAMA internal medicine, 2023)
This study compares performance on free-response clinical reasoning examinations of first- and second-year medical students vs 2 models of a popular chatbot.